Online journalism in 2011-2012 - Guallar, Javier (Anuario ThinkEPI, 2013)
Radiography of the state of digital media in 2011-2012 paying special attention to the situation in Spain, but with references to the international situation. The main points are: the crisis of the media, pay-for-content, data journalism, fact checking, apps and products for reading devices, micromedia and crowdfunding.
Keywords: Online journalism; Online newspapers; Crisis; Pay for content; Reading devices; Apps; Micromedia; Data journalism; Fact checking; Crowdfunding.